Biodiesel Production Potential from Native Tehran Oil Crops Using GIS - Hajinezhad, A.; Rahebi, S.; Abedi, S. (Engineering, Technology & Applied Science Research, 2017)
One of the main factors in the alternative fuel economy is the primary raw materials. Importing raw materials and preparation conditions for cultivation of non-native species require high expenditure. Therefore, using native species can greatly reduce production costs. Therefore in this paper, this is for the first time a comprehensive study indigenous oil plant of Tehran province and their suitable growth conditions is presented. Then three species non-edible rapeseed, cotton and barley were selected due to their feasibility of producing biodiesel. The purpose of this study is therefore to propel relevant policies in the country towards greater use of domestic raw materials and known potentials. Therefore, the potential for biodiesel production from plant sources, in this region was studied using GIS software. The present paper describes the zoning map and identifies the potential map of producing biodiesel from indigenous plant sources in Tehran province. According to the map, concentration of biodiesel production is in the central and western cities of province. This map shows that 116806.8665 hectare of land with the greatest potential to produce biodiesel. Also the potential of biodiesel production from introduced species, considering the yield per hectare and their oil content, was calculated. The results show that the potential of biodiesel production for the three species of rapeseed, cotton and barley are respectively 98117.77, 58403.43, 83516.91 tons in Tehran province. Non-edible rapeseed with the highest production potential has been introduced as a superior indigenous species for the future investments in biodiesel production in Tehran province.